Identification of four acidic amino acids that constitute the catalytic center of the RuvC Holliday junction resolvase. - Saito, A (1995)
Escherichia coli RuvC protein is a specific endonuclease that resolves Holliday junctions during homologous recombination. Since the endonucleolytic activity of RuvC requires a divalent cation and since 3 or 4 acidic residues constitute the catalytic centers of several nucleases that require a divalent cation for the catalytic activity, we examined whether any of the acidic residues of RuvC were required for the nucleolytic activity. By site-directed mutagenesis, we constructed a series of ruvC mutant genes with similar amino acid replacements in 1 of the 13 acidic residues. Among them, the mutant genes with an alteration at Asp-7, Glu-66, Asp-138, or Asp-141 could not complement UV sensitivity of a ruvC deletion strain, and the multicopy mutant genes showed a dominant negative phenotype when introduced into a wild-type strain. The products of these mutant genes were purified and their biochemical properties were studied. All of them retained the ability to form a dimer and to bind specifically to a synthetic Holliday junction. However, they showed no, or extremely reduced, endonuclease activity specific for the junction. These 4 acidic residues, which are dispersed in the primary sequence, are located in close proximity at the bottom of the putative DNA binding cleft in the three-dimensional structure. From these results, we propose that these 4 acidic residues constitute the catalytic center for the Holliday junction resolvase and that some of them play a role in coordinating a divalent metal ion in the active center.